Effect of Trailokya Vijya Vati in Various Disease – A Review - Garg, Naresh Kumar (International Research Journal of Ayurveda & Yoga, 2024)
Introduction: One of the strongest traditional medicines is Trailokya Vijaya Vati, which contains vijaya as one of its main constituents. “Trailokya Vijaya Vati” means “victory over the outer three worlds” in literal translation. According to Ayurveda, the medication is considered a “Aashukari” or drug that offers immediate comfort since it directly affects motor neurons, or “Vaat-Vaahini Naadi.” Because of this, it offers prompt relief from conditions involving different kinds of pain. Materials and Methods: Information on trailokya vijya vati in various disease was gathered from the Laghutrayi, the Brihattrayi and its commentaries, and other Ayurvedic and modern texts. Results: The binary preparation known as Trailokya Vijaya Vati, which combines Vijaya sativa with Bambusa arundianaceae, was initially documented in Rasa Vigyana, a modern Ayurvedic Alchemy and Pharmaceutics treatise. Discussion: Apasmara (seizure disorders), Rajahkashtajanya Shoola (dysmenorrhea and related symptoms), Rajayakshma (tuberculosis and similar wasting diseases), Atisara (diarrhea, colitis, IBS, IBDs, etc.), and Shoola (acute and chronic pains emerging from varied pathologies and origins) are just a few of the plethora of health conditions for which this potent formulation is renowned for producing amazing therapeutic effects. Conclusion: Trailokya Vijaya Vati improves general health and well-being by balancing the three doshas (Pitta, Kapha, and Vata) in the body The main constituents in Trailokya Vijaya Vati, a traditional medicine, are Bambusa arundinacea and Vijaya. The Ayurvedic text Rasa Vigyana describes this powerful formulation, which has been shown to have therapeutic effects for a variety of health conditions, such as anxiety, insomnia, seizures, psychological and psychosomatic disorders, dysmenorrhea, diarrhea, tuberculosis, and acute and chronic pain. The medication helps to manage seizures and has a relaxing impact on the brain.[1] Trailokya Vijaya Vati is also effective in relieving neuropathic pain. One kind of persistent pain that results from harm to the nerve system is called neuropathic pain. Trailokya Vijaya Vati’s natural components have the potential to lessen inflammation and ease neuropathic pain. Chemotherapy adverse effects can be effectively mitigated using Trailokya Vijaya Vati. Abdominal pain and renal colic